A REVIEW ON THE USE OF REMDESIVIR IN THE CURRENT VIROSIS COVID-19. - Andrade de Moura, Ana Maria Marinho (2020)
Remdesivir (GS-5734) is a drug designed for application in patients with Ebola, being used in patients in the coronavirus outbreak in the Middle East. After internalization of the drug, at the cellular level, it is converted into its active form GS-441524, and binds viral RNA polymerase (RdRp) blocking viral replication. Thus, the present study aimed to discuss the potential use of Remdesivir in coronovavirus infections. Some observed studies report promising results in the recovery of critically ill patients with COVID 19, however, there are reports of serious adverse reactions, which led to the discontinuation of therapy with this drug. Thus, measuring the efficacy and safety of Remdesivir in the treatment of COVID 19 will require broader randomized, controlled and double-blind clinical trials, so that the data and scientific information generated can guide treatment protocols for this drug.